The Joys of Teaching: Working with Language Learners in Finnish Classrooms - Alisaari Jenni; Kaukko Mervi; Heikkola Leena Maria (Routledge, Taylor & Francis Group, 2022)
This study investigated which aspects of working with multilingual students bring joy to Finnish teachers. The data was collected via an online survey from teachers working mainly in basic education in Finland. The teachers (N = 588) reported a positive stance toward multilingual learners. The greatest number of responses (44%) cited students’ intrapersonal qualities, for example students’ motivation to learn and their academic, social, and emotional successes, as a source of joy. The positive impact of diversity on the school community (14%) and the teachers’ own development (12%) were the next most common sources of joy. Teachers with more experience working with multilingual learners were more likely to name students as a source of joy; similarly, teachers at schools with more multilingual learners were more likely to reference these students as a source of joy. The findings suggest that experience with many multilingual students promotes teachers’ commitment to them.